Profil Komunikasi Matematis untuk Siswa SMP dalam Pemecahan Masalah Statistika ditinjau dari Perbedaan Gender - Allisa Madepera; Ali Shodiqin; Muhtarom Muhtarom (Perkumpulan Kualitama Edukatika Indonesia, 2021)
This study aims to determine how the mathematics communication profile of junior high school students in solving statistical problems based on gender differences. This research is descriptive qualitative. The triangulation used in this research is the triangulation of techniques / methods. The results showed that on indicators linking everyday language with mathematics language, students with masculine gender got lower results than students with feminine gender by a difference of 16.7%. Meanwhile, for the second indicator, namely reflecting / describing mathematical statements in tabular form, students with masculine gender were superior to students with feminine gender by a difference of 16.7% as well. Furthermore, for indicators of understanding, evaluating and interpreting mathematical ideas in solving problems in writing, students with feminine gender are superior to students with masculine gender by a difference of 33.37%. for the last indicator, namely concluding the answers according to the questions, students with masculine gender get lower results again than students with feminine gender by a difference of 50%.